PENGEMBANGAN KAPASITAS SUMBER DAYA MANUSIA DALAM MEMBANGUN PELAYANAN PUBLIK PRIMA DI LINGKUNGAN PEMERINTAHAN DAERAH KOTA BANDUNG - Rusmanto, Wieky (Jurnal Progress Administrasi Publik, 2023)
Developing the quality of Human Resources is essential to realizing excellent public services. Based on this understanding, this article intends to describe and analyze the process of developing Human Resources capacity in building excellent public services in Bandung. The research method used is a qualitative research method with a descriptive approach. The research results show that efforts to develop human resource capacity in realizing excellent public services are shown through three stages: First, building knowledge about public services for local government officials in the local government environment in Bandung City. Second, building skills in providing excellent service for citizens in Bandung. Third, building a friendly and service-oriented attitude and behavior for the regional government apparatus of Bandung. These three efforts are expected to be able to realize excellent service in the city of Bandung through the process of developing human resources for government officials in the regional government of the city of Bandung.   Keywords: Organizational Capacity; Human Resources; Public Services.